Early life adversity, contact with children’s social care services and educational outcomes at age 16 years: UK birth cohort study with linkage to national administrative records - John Macleod; Alison Teyhan; Andy Boyd; Dinithi Wijedasa (BMJ Open)
Objectives To use record linkage of birth cohort and administrative data to study educational outcomes of children who are looked-after (in public care) and in need (social services involvement), and examine the role of early life factors.Setting, design Prospective observational study of children from the Avon Longitudinal Study of Parents and Children (ALSPAC), which recruited pregnant women in and around Bristol, UK in the early 1990s. ALSPAC was linked to the annual Children Looked-After (CLA) Data Return and Children In Need (CIN) Census. Educational outcomes at 16 years were obtained through linkage to the National Pupil Database (NPD). These included passing 5+ good GCSEs (grades A*-C, including English and Maths). Covariates included early life adversity and social position.Participants 12 868 ALSPAC participants were linked to the NPD. The sample for the main educational outcomes analyses comprised 9545 children from the ALSPAC core sample who had complete education data.Results Overall, of the 12 868 ALSPAC participants linked to NPD data, 137 had a CLA record and a further 209 a CIN record during adolescence. These children were more disadvantaged than their peers and had little active study participation beyond infancy. In the main educational outcomes analyses, achievement of 5+ good GCSEs was low in the CLA (OR 0.14, 95% CI 0.05 to 0.35) and CIN (0.11, 0.05 to 0.27) groups relative to their peers. Measured early life factors explained little of this difference.Conclusions Data linkage enabled the study of educational outcomes in children with social services contact. These children had substantially worse educational outcomes relative to their peers, for reasons likely to be multifactorial.